Management of impacted maxillary canine with surgical exposure and alignment by orthodontic treatment - Meralda Rossy Syahdinda; Alexander Patera Nugraha; Ari Triwardhani; Tengku Natasha Eleena binti Tengku Ahmad Noor (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2022)
Background: Maxillary canines play a critical point in creating an aesthetic smile as they support the part of facial muscle. Canines are also the second most frequently impacted teeth after the third molars. In some cases, it is possible to retract canines into their correct position by orthodontics treatment. Purpose: This article highlighted a treatment option with surgical exposure, in which a maxillary canine was impacted. It presented gradual steps from pre-surgical to post-surgical orthodontic treatment. Case: A 16 years old female patient referred to Orthodontic Department by Oral Surgeon for pre-surgical orthodontic treatment of her impacted maxillary canine. Case Management: After pre-surgical orthodontic treatment, the impacted canine was surgically exposed by closed technique since open surgical exposure might need excessive removal of the surrounding bone. Traction was given through a gold chain which attached to the palatal surface of the impacted canine. The tooth was ideally positioned with fixed orthodontic appliances. The permanent right maxillary canine was successfully positioned into proper alignment with the remaining teeth. Aesthetic smile was improved. Conclusion: Malocclusion with impacted canine was successfully treated with MBT orthodontic prescription combined with gold chain that can retract the impacted canine into its physiological position and the patient was satisfied with the aesthetic result.